KONSEP ILMU DALAM PERSFEKTIF AL-QUR’AN - Andi Baso Darussalam; Achmad Abu Bakar; M. Sadik Sabry (Risalah, Jurnal Pendidikan dan Studi Islam, 2021)
This study examines the concept of science in the effectiveness of the Qur'an, with two problem formulations namely how the meaning of science in the Qur'an? how is the embodiment of science in the Qur'an?.This study uses verse analysis and interpretation of the Quran with mauduiy interpretation method. As for the conclusion that the use of the word 'ilm with all its derivations in the Qur'an found two purposes, science in the general sense and science in a special sense that translated as scientific knowledge, but both must be given a scientific predicate in the sense of containing the terms of truth. The realization of science in the Qur'an indicates the existence of three components involved in the process of discovery of science, namely; al-sama (hearing), al-bashar (vision) and fu'ad (understanding). These three components are potential tools that humans have to acquire knowledge.